Sharing with crowds - Hafeez, Saima (Economic and business review, 2025)
n this paper, we provide an overview of the existing research on emotions in crowdfunding and integrate it using a bibliometric analysis of publication data from the decade 2013–2023. Our analysis includes a citation and cocitation analysis, a productivity analysis, a co-occurrence analysis, and a topic analysis based on abstracts. We find that the Journal of Business Venturing and Entrepreneurship Theory and Practice are the most prominent journals publishing research at the intersection of emotions and crowdfunding. The coword analysis shows that current and frequently discussed topics are related to emotions, sentiment analysis, reward-based crowdfunding, machine learning, and blockchain. Furthermore, our results show a significant increase in interdisciplinary approaches that integrate psychological and economic perspectives to better understand backers’ behavior. Finally, we point to a gap in the understanding of the long-term effects of emotions on crowdfunding campaigns and suggest a possible direction for future studies.
Keywords: bibliometric analysis; bibliometrična analiza; crowdfunding; investicije; investments; množično financiranje